Strategi Peningkatan Pendapatan Rumah Sakit Berdasarkan Analisis SWOT - Nina Fentiana; Daniel Ginting (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The hospital as a business entity in the service sector has its own mission, which is to provide quality services with the achievement of patient satisfaction which is marked by reduced complaints from customers, increased visits so that it shows high company performance. SWOT analysis is a systematic identification of various factors to formulate a company strategy. This research is to find the right strategic opportunity or opportunity, where there is a large market share that allows hospitals to grow and develop. The focus of this research is a strategic plan in an effort to increase hospital income by analyzing a picture of hospital performance in the last 3 years from 2017 to 2019. The study was conducted using a qualitative approach in one of the hospitals in Langsa City. Based on the results of the SWOT diagram, the strategic plan that will be implemented to increase hospital income is to implement standardization of human resources (number of SOP educational task descriptions), cost efficiency, superior services, patient satisfaction surveys and implement efficiency of direct general financing and investment.